Forecasting Macroeconomic Variables in Indonesia Using the Vector Autoregressive Method - Nonong Amalita; Syafriandi Syafriandi; Yenni Kurniawati; Mira Meilisa; Bunga Nafandra (UIN Sumatera Utara, 2026)
This study aims to analyze the dynamic relationship and predict inflation, the rupiah exchange rate, oil and gas exports, and BI interest rates in Indonesia. The Vector Autoregressive (VAR) method was used with monthly data from January 2015 to September 2025, the best model obtained was VAR (2). The Granger causality test results show that most variables are dominated by their own lag effects. Impulse response analysis shows that shocks are temporary and subside in the medium term. Forecast results for October 2025–September 2026 shows relatively stable inflation in the range of 2.42–2.70%. The rupiah exchange rate is expected to depreciate moderately by around 1.4%. Meanwhile, oil and gas exports declined significantly by 3.9%, and the BI interest rate is expected to fall by 12.8% to 4.14%. These findings indicate that Indonesia's macroeconomic stability is dominated by internal dynamics, so monetary policy focuses on inflation and the exchange rate.